2016
DOI: 10.1155/2016/3628501
|View full text |Cite
|
Sign up to set email alerts
|

TNFαAffects Ciliary Beat Response to Increased Viscosity in Human Pediatric Airway Epithelium

Abstract: In airway epithelium, mucociliary clearance (MCC) velocity depends on the ciliary beat frequency (CBF), and it is affected by mucus viscoelastic properties. Local inflammation induces secretion of cytokines (TNFα) that can alter mucus viscosity; however airway ciliated cells have an autoregulatory mechanism to prevent the collapse of CBF in response to increase in mucus viscosity, mechanism that is associated with an increment in intracellular Ca+2 level ([Ca2+]i). We studied the effect of TNFα on the autoregu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…The movement of cilia is dependent, at least partially, on cyclic nucleotides and in particular on cAMPs [35]. In addition, active ion transport, such as that of Ca 2+ , Na + and Cl − , plays an important role in regulating mucus viscosity and mucociliary clearance [36,37], and both Ca 2+ and Na + can be transported through cyclic nucleotide-gated channels [38]. Notably, previous studies have suggested that neurohormonal signalling regulates cyclic guanosine monophosphate (cGMP) induced mucin secretion [39] and the expression of GDNF, the gene encoding for a neurotrophic factor involved in lung development, is associated with CMH in COPD [40].…”
Section: Discussionmentioning
confidence: 99%
“…The movement of cilia is dependent, at least partially, on cyclic nucleotides and in particular on cAMPs [35]. In addition, active ion transport, such as that of Ca 2+ , Na + and Cl − , plays an important role in regulating mucus viscosity and mucociliary clearance [36,37], and both Ca 2+ and Na + can be transported through cyclic nucleotide-gated channels [38]. Notably, previous studies have suggested that neurohormonal signalling regulates cyclic guanosine monophosphate (cGMP) induced mucin secretion [39] and the expression of GDNF, the gene encoding for a neurotrophic factor involved in lung development, is associated with CMH in COPD [40].…”
Section: Discussionmentioning
confidence: 99%
“…Proper mucus production and coordinated ciliary activity are required for effective mucociliary clearance. It has been shown in several studies that inflammatory cytokines are effective on NMC (15)(16)(17). In their study, Gonzalez et al (16) have revealed that TNF α, a proinflammatory cytokine, inhibits viscosity-related ciliary activity in human respiratory cultures.…”
Section: Discussionmentioning
confidence: 97%
“…It has been shown in several studies that inflammatory cytokines are effective on NMC (15)(16)(17). In their study, Gonzalez et al (16) have revealed that TNF α, a proinflammatory cytokine, inhibits viscosity-related ciliary activity in human respiratory cultures. Disruption of NMC increases the risk of infection in the upper and lower respiratory tract (9).…”
Section: Discussionmentioning
confidence: 97%